PENGARUH KESADARAN WAJIB PAJAK DAN KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI WILAYAH KPP PRATAMA PANDEGLANG - Rudiyanto Rudiyanto; Hidayatullah Hidayatullah (Universitas La Tansa Mashiro, 2016)
The number of tax payers is increase for years . But, it is not balanced with the level of tax compliance. The compliance problem becomes an obstacle in optimizing the tax revenue. This study examines the level of compliance of individual taxpayers in Pandeglang by using several independent variables s uch as awareness of the tax payer and the service tax authorities. The purpose of this study was to analyze the influence of awareness of the taxpayer and the service tax authorities against an individual taxpayer compliance. The population of this study is individual taxpayers. Based on data from the KPP Pratama Pandeglang, until the end of 2015 there were 89.193 individual taxpayers. Not all population have been used in this study to the time and cost efficiency. Therefore, carried out the sampling. Sampl ing was done by simple random sampling method. The number of sample is 100 people. Primary data collection method used is a survey method using questionnaires media. Data analysis techniques used in this study is the technique of multiple regression analys is. Based on the results of the analysis undertaken concluded that awareness of the tax payer and the service tax authorities have a positive and significant impact on taxpayer compliance.